Isolation of cellulose nanocrystals from brown seaweed, Sargassum fluitans, for development of alginate nanocomposite film. Issue 4 (22nd June 2020) - Doh, Hansol; Whiteside, William Scott
Abstract: Alginate nanocomposite (Alg/cellulose nanocrystals [CNCs]) films reinforced with CNCs isolated from Sargassum fluitans . Sargassum spp. have been treated as waste in the North Atlantic Ocean. CNCs were isolated by acid hydrolysis and mechanical treatment and used as reinforcing agents to obtain Alg/CNCs film by addition at different concentrations (1%, 3%, 5%, and 10%). Morphological, mechanical, and barrier properties of the bionanocomposites were analyzed. CNCs layers can be observed in the alginate polymer matrix by scanning electron microscopy observation and addition of 1%, 3%, and 5% CNCs (wt/wt) enhanced the tensile strength of Alg/CNCs film. Water vapor, oxygen permeability, and light transmittance decreased gradually with increasing addition of CNCs. Chemical interaction between CNCs and alginate was analyzed with Fourier transform infrared spectrometry. Thermogravimetric analysis and differential scanning calorimeter data suggested the addition of CNCs can improve the thermal properties of Alg/CNCs films. Therefore, Alg/CNCs films can potentially be used for food packaging systems with enhanced properties. Abstract : The cellulose nanocrystals (CNCs) are isolated from brown seaweed, Sargassum fluitans, which have recently caused both environmental issues and economic losses in North Atlantic sea. Alginate nanocomposite film reinforced with isolated CNCs was tested for proving improvements of the physicochemical, mechanical, barrier, and thermal properties.